Modern currency wars: The United States versus Japan - Ronald McKinnon; Zhao Liu (Asian Development Bank Institute (ADBI), 2013)
In the currency wars of the 1920s and 1930s, various nations fell off the gold standard and in so doing experienced deep devaluations. But under the postwar dollar standard, the central position of the US was key to maintaining the peace, until the Bretton Woods system of fixed dollar exchange parities fell apart after the so-called "Nixon Shock" of 1971. Now, without much fear of retaliation, the US can initiate more limited currency warfare - as with American "Japan bashing" from the late 1970s to mid-1990s to appreciate the yen, or "China bashing" since 2002 to appreciate the renminbi. Japan succumbed to this bashing, and the yen appreciated too much in 1985, with the result that Japan fell into a zero-interest liquidity trap and economic stagnation for almost two decades. However, in 2013, through massive quantitative easing by the Bank of Japan (BOJ), the yen depreciated about 25% against the dollar, stoking fears of a return to Japan bashing by the US. However, this sharp depreciation simply restored the purchasing power parity of the yen with the dollar so it should even out in the long run. In the short run, we show that yen depreciation could adversely affect the smaller East Asian economies. Since 2008, quantitative easing by the BOJ has been similar to that carried out by the US Federal Reserve, the Bank of England, and the European Central Bank. So the BOJ can only be faulted as a currency belligerent if there is a further significant yen depreciation. Led by the US, now all mature industrial countries are addicted to near-zero interest liquidity traps in both the short and long terms. These ultra low interest rates are causing lasting damage to the countries' financial systems, and to those of emerging markets, which naturally have higher interest rates. But exiting from the trap creates a risk of chaos in long-term bond markets and is proving surprisingly difficult.
Keywords: F31; F32; 330; currency wars; liquidity trap; quantitative easing; dollar versus yen; purchasing power parity; Währungssystem; Währungswettbewerb; US-Dollar; Yen